Escândalos financeiros: a problemática das falhas de controle de mesas de instituições financeiras durante os anos de 1995 a 2008 - Hermann Filho, Roberto Max (2011)
Since the failure of Barings Bank in 1995, the corporate world has experienced a series of financial scandals, which losses have gone up exponentially and reached almost five billion Euros in the Société Générale case. Those losses are generated by the dealing desks, where traders take advantage of, amongst other things, a broken control framework to take non authorized positions that resulted in severe losses due to unfavorable market moves (rogue trader type of fraud). The objective of this work is to conduct a case study approach comparing the key deficiencies amongst five important losses: Baring Bank, Allied Irish Bank, Enron, National Australian Bank and Société Générale. The key finding, which can be very helpful to prevent occurrence of new similar cases, brings up the common causes in all cases: internal environment lenient with internal controls and ethical standards; inadequate measurement and understanding of risks; ineffective systems and controls carried out with scarce and unqualified human resources; failures related to information sharing, communication and monitoring